The Israel Merchant Marine: An Economic Appraisal - Bank of Israel (Jerusalem: Research Department, Bank of Israel, 1962)
Israel shipping has reached a stage where its future development poses a number of serious problems, and an appraisal of its past achievements and of shipping markets becomes indispensable for the planning of further expansion of the Israel merchant marine. This study therefore has a threefold aim: 1) to analyze the economic performance of Israel shipping during 1958 and 1959; 2) to analyze Israel's shipping markets; and 3) to assess the probable requirements for 1965.
ne 22/03/2018
Loan
Keywords: Merchant Marine